2008
DOI: 10.1002/joc.1767
|View full text |Cite
|
Sign up to set email alerts
|

Using regional wind fields to improve general circulation model forecasts of July–September Sahel rainfall

Abstract: This study develops and applies a model output statistics (MOS) approach for correcting poor general circulation model (GCM) seasonal rainfall predictions over the Sahel region of West Africa. It illustrates a methodology for approaching the MOS prediction of regional rainfall, drawing on knowledge of the regional circulation system. The ECHAM4.5 GCM has very little skill in predicting July-September Sahel rainfall. However, the GCM is much more capable of reproducing the regional wind circulation at 925 hPa, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 31 publications
(55 reference statements)
4
35
0
Order By: Relevance
“…For AGCM forecasts of Sahel rainfall, the published literature contains no clear systematic improvements on this approach. Applying the persistence approach, although June SST showed good skill in Ndiaye et al (2009), prediction skill from May and April SST was substantially reduced, even after applying the MOS system.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…For AGCM forecasts of Sahel rainfall, the published literature contains no clear systematic improvements on this approach. Applying the persistence approach, although June SST showed good skill in Ndiaye et al (2009), prediction skill from May and April SST was substantially reduced, even after applying the MOS system.…”
Section: Introductionmentioning
confidence: 83%
“…The approach taken in Ndiaye et al (2009), to address the problem with AGCM simulations of Sahel rainfall, was to focus on indices of the regional circulation system predicted by the AGCM (ECHAM4.5) and to use the indices in a model output statistics (MOS) to predict Sahel rainfall. The ECHAM4.5 AGCM is typical in its poor level of skill for Sahel rainfall; however, using the low-level wind field over the tropical Atlantic and western part of West Africa, a level of skill in predicting Sahel rainfall is achieved that is comparable with the small number of AGCMs that have been able to successfully represent the impact of SST directly on Sahel rainfall (e.g., Giannini et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Light spatial smoothing has also been done to reduce noise. Other modifications include selected spatial model output statistics (MOS) corrections of systematic errors of the individual AGCMs for precipitation for specific regions using CCA (Ndiaye et al 2009;Tippett et al 2003;Landman and Goddard 2002); a nudging toward reduction (enhancement) of probabilities for below-normal (above normal) temperature, partly in response to a diagnostic verification of IRI's forecasts during 1997-2000 (Wilks and Godfrey 2002); and making the forecasts more consistent with those of other meteorological centers or regional climate outlook forums.…”
Section: Final Forecastmentioning
confidence: 99%
“…Model projections of future climate vary dramatically between much wetter and much drier conditions (Druyan 2011), and this has heightened the ambition to identify which models are more or less credible. There are already good examples of process-based model evaluation for West Africa, including investigation of the meridional circulation (Cook and Vizy 2006;James et al 2015), the AEJ (Caminade et al 2006;Abiodun et al 2011), AEWs , the Saharan heat low (Biasutti et al 2009), jet-rainfall coupling (Whittleston et al 2017), and analysis across a range of time scales (Cook and Vizy 2006;Ndiaye et al 2009;Birch and Parker 2014;Diasso and Abiodun 2017;Vellinga et al 2016). This research has shown that many models do not produce a monsoon at all: the rainfall maximum does not move onto the continent during the boreal summer (Cook and Vizy 2006), at least in part because of a warm SST bias in the Gulf of Guinea (Roehrig et al 2013).…”
Section: Pan-africanmentioning
confidence: 99%